PENGARUH KEDISIPLINAN KERJA TERHADAP KINERJA PEGAWAI PT LEMBAGA KEUANGAN MIKRO (LKM)BADAN KREDIT DESA KUTOARJO - Elsa Fentika (Prospect : Jurnal Manajemen dan Akuntansi, 2022)
This research aims to find out whether work discipline has a positive and significant effect on the performance of employees of PT Microfinance Institution (LKM) Kutoarjo Village Credit Agency. The data source uses a questionnaire. The population in this study were 16 employees of the Kutoarjo Village Credit Agency Microfinance Institution. The sample in this study was 16 people. Data analysis techniques include simple linear regression analysis coefficients, coefficients of determination, and T tests. The results of the t test show that the t value of the work discipline variable is greater than t table (7.312 > 1.761) or the sig value is (0.000 < 0.05), meaning that the work discipline variable has a significant effect. positive and significant on performance so that the hypothesis is accepted.